Recycled polyester resin and method for producing recycled polyester resin

The production of recycled polyester resin through a depolymerization, filtration, and polycondensation process addresses the challenge of foreign matter contamination, resulting in a high-quality resin suitable for various polyester products with enhanced thermal stability and productivity.

JP2025071234APending Publication Date: 2025-05-02UNITIKA LTD +2
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2025025658
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-02-07
Filing Date
2025-02-20
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Current methods for producing recycled polyester resin struggle to completely remove foreign matter, particularly from non-polyester resins, leading to contamination and reduced quality of the final product, which affects the productivity and stability of processes like melt spinning and film formation.

Method used

A recycled polyester resin is produced using a specific process that involves treating recycled polyester raw materials with a depolymerization step using an ethylene terephthalate oligomer and ethylene glycol, followed by filtration and polycondensation under controlled conditions to minimize foreign matter and achieve desired chemical and thermal properties.

Benefits of technology

The resulting recycled polyester resin has a high thermal stability, excellent heat resistance, and a low content of foreign matter, enabling the production of high-quality polyester products, including ultra-fine fibers and films, with improved productivity and operational stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025071234000001
    Figure 2025071234000001
  • Figure 2025071234000002
    Figure 2025071234000002
  • Figure 2025071234000003
    Figure 2025071234000003
Patent Text Reader

Abstract

To provide a recycled polyester resin that can be used in the production of various forms of polyester products, the recycled polyester resin obtained from a recycled polyester raw material derived from a used polyester product, or a recycled polyester raw material derived from scrap or the like generated in the process of producing a polyester resin or product.SOLUTION: A polyester resin contains a component derived from at least one recycled polyester raw material of a) a used polyester product and b) an unemployed polyester resin generated in the process of producing a polyester product. (1) When the total content of all glycol components is 100 mol%, the content of diethylene glycol is 4 mol% or less, (2) a carboxyl terminal group concentration is 30 equiv. / t or less, and (3) an average pressure rise rate is 0.6 MPa / h or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a novel recycled polyester resin and a method for producing the same. In particular, the present invention relates to a recycled polyester resin produced from recycled polyester raw materials derived from used polyester products as well as recycled polyester raw materials derived from unused polyester generated in the process of producing polyester products, which has a low amount of foreign matter mixed in and can be processed into various molded products in the same way as virgin polyester resin, and a method for producing the same. [Background technology]

[0002] Polyethylene terephthalate (PET) has a high melting point, is resistant to chemicals, and is relatively low cost, so it is widely used in fibers, films, plastic bottles, and other molded products. These polyester products inevitably generate waste during the manufacturing and processing stages, and are often disposed of after use. However, when incinerated, high heat is generated, causing significant damage to the incinerator and shortening its lifespan. On the other hand, when not incinerated, it does not decompose and will remain semi-permanently.

[0003] In recent years, it has become a problem that plastics are a major cause of marine pollution, with a worldwide movement to reduce the use of plastics and switch to biodegradable plastics. Plastics are a major cause of marine pollution, and in recent years, plastics have been found to be harmful to marine ecosystems. Plastics are a major cause of marine pollution, and in recent years, plastics have been found to be harmful to marine ecosystems.

[0004] In light of these environmental issues, various methods of recycling are being used to reuse resources. For polyester products such as PET, in addition to recycling polyester waste generated during the manufacturing process, methods are being considered for collecting products that were once on the market and then discarded and reusing them as raw materials. In particular, in recent years, textile products that have been given the Eco Mark, which is certified as having achieved a certain recycling rate, have become widespread. Various methods have been proposed for recycling polyester raw materials, such as polyester waste generated in the manufacturing process or recovered used polyester products.

[0005] For example, there have been proposed a method of adding methanol to PET scraps to decompose them into dimethylene terephthalate (hereinafter sometimes referred to as "DMT") and ethylene glycol (hereinafter sometimes referred to as "EG") (Patent Document 1), a method of adding EG to PET scraps to depolymerize them, and then adding methanol to recover DMT (Patent Document 2), and a method of depolymerizing PET scraps with EG to form oligomers, which are then used in a polycondensation reaction (Patent Document 3).

[0006] Incidentally, impurities that can become a problem when recycling PET bottles and other products that have already been made include various additives added to the polyester resin, as well as items attached to the bottle itself, such as a) caps (aluminum, polypropylene, polyethylene), b) inner stoppers, c) liners (polypropylene, polyethylene), d) labels (paper, resins such as polystyrene, ink), e) adhesives, and f) printing ink.

[0007] Generally, as a pretreatment step for the recycling process, the collected PET bottles are put through a vibrating sieve to remove sand, metal, etc. The PET bottles are then washed, and the colored bottles are separated before being roughly crushed. Labels, etc. are then removed by wind separation. Furthermore, aluminum pieces from the caps, etc. are removed and the PET bottle pieces are finely crushed. Components such as adhesives, proteins, and mold are removed by high-temperature alkaline washing, and different components such as polypropylene and polyethylene are separated by differences in specific gravity.

[0008] However, even after going through these steps, it is difficult to completely separate and remove non-polyester resins, particularly polypropylene, polyethylene, polystyrene, etc., from PET resin.

[0009] For example, even if the production of recycled polyester resin is attempted by the recycling methods described in Patent Documents 1 to 4, the removal of foreign matter derived from non-polyester resins cannot be sufficiently performed, and the amount of foreign matter mixed in cannot be sufficiently reduced, making it difficult to obtain a product with the same quality as virgin polyester resin. If the amount of foreign matter mixed in is not sufficiently reduced in this way, the pressure rise rate of the filtration filter in the spinning process or film-forming process is fast, long-term continuous operation is not possible, and processing operability becomes very poor. Moreover, the methods described in Patent Documents 1 to 3 require a large amount of cost for the installation, operation, maintenance, etc. of the recovery device, and there is room for improvement in terms of practicality. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Special Publication No. 42-8855 [Patent Document 2] Japanese Patent Publication No. 48-62732 [Patent Document 3] Japanese Patent Application Laid-Open No. 60-248646 [Patent Document 4] JP 2005-171138 A Summary of the Invention [Problem to be solved by the invention]

[0011] As described above, a method for obtaining recycled polyester resin from which not only various inorganic substances but also foreign matter derived from non-polyester resins has been sufficiently removed and from which various products can be obtained in the same way as with virgin polyester resin has not yet been developed.

[0012] In particular, when polyester resin is melt-spun to produce fibers, the amount of foreign matter mixed in has a significant effect on productivity. When producing fibers, resin is extruded from a nozzle with a small hole diameter in the melt spinning process, and the extruded filaments are taken up by rollers, and if necessary, they are stretched or heat-treated, and then wound up. In this case, if resin containing foreign matter is used, thread breakage is likely to occur in the melt spinning, stretching / heat-treatment, and winding processes, making it difficult to carry out stable production.

[0013] This problem becomes more pronounced when attempting to produce finer fibers. For example, it has not yet been realized to obtain ultrafine fibers, particularly those with a single fiber size of 0.5 dtex or less, by melt spinning recycled polyester resin produced using polyester waste or the like as a raw material.

[0014] Therefore, a main object of the present invention is to solve the above problems and provide a recycled polyester resin that can be used to produce polyester products of various forms, using recycled polyester raw materials derived from used polyester products or recycled polyester raw materials derived from scraps generated in the process of producing polyester resins and products. [Means for solving the problem]

[0015] Means for Solving the Problems of the Prior Art The present inventors have conducted intensive research in light of the problems of the prior art and have found that the above-mentioned object can be achieved by a polyester resin obtained by treating recycled polyester raw materials in a specific process, thereby completing the present invention.

[0016] That is, the present invention relates to the following recycled polyester resin and its production method. 1. A polyester resin containing a component derived from at least one recycled polyester raw material, which is a) a used polyester product and b) an unused polyester resin generated in the process of manufacturing a polyester product, (1) When the total amount of all glycol components is 100 mol %, the diethylene glycol content is 4 mol % or less, (2) The carboxyl end group concentration is 30 equivalents / t or less, (3) The average pressure rise rate is 0.6 MPa / h or less (however, the average pressure rise rate is a value calculated by the following procedure: a pressure rise tester including an extruder and a pressure sensor is used, a stainless steel filter (nominal mesh size: 1400 mesh, weave: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical wire diameter: 0.07 mm, horizontal wire diameter: 0.04 mm, filtration grain size: 12 μm) is set at the tip of the extruder, polyester resin is melted at 300° C. in the extruder, and the melt is extruded from the filter at a discharge rate of 29.0 g / min. The pressure value at the start of extrusion is defined as the "initial pressure value (MPa)" and the pressure value at the time of continuous extrusion for 12 hours thereafter is defined as the "final pressure value (MPa)." Based on these pressure values, the above average pressure rise rate is calculated by the following formula A: Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) · · · A), A recycled polyester resin. 2. Fibers containing the recycled polyester resin described in item 1 above. 3. A blow molded product containing the recycled polyester resin described in item 1 above. 4. A film containing the recycled polyester resin described in item 1. 5. A method for producing a recycled polyester resin using at least one recycled polyester raw material, which is a) a used polyester product and b) an unused polyester generated in a process for producing a polyester product, comprising: (1) a step of adding the raw material to a mixture containing ethylene terephthalate oligomer and ethylene glycol so that the molar ratio of total glycol components / total acid components becomes 1.08 to 1.35, and performing depolymerization under heat treatment conditions of 245 to 280° C. to obtain a reaction product containing a depolymerization product; (2) passing the reaction product through a filter having a filtration particle size of 10 to 25 μm to recover a filtrate; (3) adding a polymerization catalyst to the filtrate and carrying out a polycondensation reaction of the depolymerization product at a temperature of 260° C. or higher and a reduced pressure of 1.0 hPa or lower; A method for producing a recycled polyester resin, comprising: 6. The manufacturing method according to item 5, wherein the raw material contains 40% by mass or more of at least one of a) used polyester products and b) unused polyester resins generated in the process of manufacturing polyester products. Effect of the Invention

[0017] According to the present invention, it is possible to provide a recycled polyester resin that can be used for producing polyester products of various forms, using recycled polyester raw materials derived from used polyester products or recycled polyester raw materials derived from polyester scraps generated in the process of producing polyester resins and products.

[0018] In particular, the present invention can provide a recycled polyester resin that uses a high proportion of at least one type of recycled polyester raw material, i.e., a) used polyester product and b) unused polyester generated in the process of manufacturing a polyester product, while containing little foreign matter and having a carboxyl end group concentration and a diethylene glycol content controlled within a specific range. As a result, for example, in the process of obtaining fibers by melt spinning, the process of obtaining sheets or films by membrane formation, and the process of obtaining molded products such as bottles, continuous operation over a relatively long period of time is possible, and products in various forms can be produced with good productivity.

[0019] Furthermore, products (fibers, sheets, films, bottles, etc.) obtained from the recycled polyester resin of the present invention have high thermal stability and excellent heat resistance, and can exhibit excellent quality similar to those produced using virgin polyester resin.

[0020] According to the method for producing recycled polyester resin of the present invention, it is possible to efficiently and reliably produce recycled polyester resin which is low in the amount of foreign matter as described above, has high thermal stability, and is excellent in heat resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] 1. Recycled polyester resin The recycled polyester resin of the present invention (the resin of the present invention) is a polyester resin containing a component derived from at least one recycled polyester raw material, which is a) a used polyester product and b) an unused polyester generated in a process for manufacturing a polyester product, (1) When the total amount of all glycol components is 100 mol %, the diethylene glycol content is 4 mol % or less, (2) The carboxyl end group concentration is 30 equivalents / t or less, (3) The average pressure rise rate is 0.6 MPa / h or less (however, the average pressure rise rate is a value calculated by the following procedure: a pressure rise tester including an extruder and a pressure sensor is used, a stainless steel filter (nominal mesh size: 1400 mesh, weave: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical wire diameter: 0.07 mm, horizontal wire diameter: 0.04 mm, filtration grain size: 12 μm) is set at the tip of the extruder, polyester resin is melted at 300° C. in the extruder, and the melt is extruded from the filter at a discharge rate of 29.0 g / min. The pressure value at the start of extrusion is defined as the "initial pressure value (MPa)" and the pressure value at the time of continuous extrusion for 12 hours thereafter is defined as the "final pressure value (MPa)." Based on these pressure values, the above average pressure rise rate is calculated by the following formula A: Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) A) It is characterized by:

[0022] The resin components constituting the resin of the present invention include components derived from at least one type of recycled polyester raw material, i.e., a) used polyester products and b) unused polyester generated in the process of manufacturing polyester products. These components form part of the polyester constituting the resin of the present invention.

[0023] Examples of used polyester products in the above category a) include polyester molded products (including fibers) that were once on the market and then collected after use, etc. Representative examples of such products include containers such as PET bottles and packaging materials.

[0024] The unadopted polyester generated in the manufacturing process of polyester products mentioned in b) above is polyester that did not reach the stage of commercialization. Examples of such unadopted polyester include resin pellets that do not meet the specifications, materials that are no longer needed during molding, pieces cut during molding, scraps (polyester scraps) generated during molding and processing, cut-up pieces of transitional products generated when changing brands, and cut-up pieces of prototypes and defective products.

[0025] The above-mentioned a) and b) are not limited in their form, and may be pelletized by further processing such as crushing and cutting as necessary, or may be melted and pelletized. The above-mentioned a) and b) may be used alone or in combination.

[0026] The recycled polyester raw materials a) and b) above may be either crystalline or amorphous. Therefore, for example, pellets of amorphous polyester waste that have not been heat-treated, crystalline pellets that have been heat-treated, or a mixture of crystalline pellets and amorphous pellets can be used. In the present invention, it is preferable to use crystalline recycled polyester raw materials in order to prevent the pellets from fusing together, particularly when being put into a can or during the depolymerization reaction. Therefore, the materials a) or b) above that have been crystallized by heat treatment (crystallized pellets, etc.) can be suitably used.

[0027] The properties of the recycled polyester raw materials in a) and b) above are not limited, and may be in the form of a) and b) above, or may be in the form of cut pieces, crushed materials (powders), etc. obtained by further processing such as cutting and crushing, as well as in the form of solids such as molded bodies (pellets, etc.) obtained by molding these. More specifically, pellets obtained by cooling and cutting melted polyester waste, and cut pieces obtained by finely cutting polyester molded products such as PET bottles are exemplified. In addition, the above-mentioned cut pieces, crushed materials (powders), etc. may be in the form of a liquid (dispersion or solution) obtained by dispersing or dissolving them in a solvent. When producing polyester products using these raw materials, they can be melted at a temperature above their melting point as necessary and charged into a can as a melt.

[0028] The recycled polyester resin of the present invention (resin of the present invention) contains a component derived from at least one recycled polyester raw material of a) used polyester products and b) unused polyester generated in the process of manufacturing polyester products, and the content of the component in the resin of the present invention is preferably 40% by mass or more, and more preferably 50% by mass or more. If the content is less than 40% by mass, the recycling rate of unused polyester decreases. The upper limit of the content is not particularly limited, but according to the manufacturing method of the present invention described later, it is possible to easily obtain a recycled polyester resin with a recycled polyester raw material content of 40 to 80% by mass.

[0029] In the resin of the present invention, when the total amount of all glycol components is 100 mol%, the diethylene glycol content is 4 mol% or less, and preferably 3.5 mol% or less. In particular, in the resin of the present invention obtained by the production method of the present invention, ethylene glycol is used as one of the raw materials, and diethylene glycol may be generated as a by-product. The resin of the present invention has a small amount of diethylene glycol as a by-product, and excellent thermal stability can be obtained by setting the diethylene glycol content to 4 mol% or less. Therefore, it is possible to obtain molded products such as fibers, injection molded products, various blow molded products, sheets, and films with good productivity. The lower limit of the diethylene glycol content can be, for example, about 0.5 mol%, but is not limited thereto.

[0030] The resin of the present invention has a carboxyl end group concentration of 30 equivalents / t or less, preferably 25 equivalents / t or less, and most preferably 20 equivalents / t or less. By making the carboxyl end group concentration 30 equivalents / t or less, it has excellent heat resistance, and it is possible to obtain molded products with excellent heat resistance by various molding methods. The lower limit of the carboxyl end group concentration can be, for example, about 5 equivalents / t, but is not limited thereto.

[0031] The resin of the present invention has an average pressure rise rate of 0.6 MPa / h or less, preferably 0.5 MPa / h or less, and more preferably 0.4 MPa / h or less, as measured by the following method. The average pressure rise rate in the present invention is an index of the amount of foreign matter derived from various inorganic substances, foreign matter derived from non-polyester resins, etc., and the lower the average pressure rise rate, the lower the amount of foreign matter. By having an average pressure rise rate of 0.6 MPa / h or less, it is possible to produce ultrafine fibers having a single fiber fineness of 0.5 decitex or less, for example, by melt spinning. The lower limit of the average pressure rise rate can be, for example, about 0.01 MPa / h, but is not limited thereto.

[0032] The average pressure rise rate was measured by using a pressure rise tester including an extruder and a pressure sensor, setting the filter at the tip of the extruder, melting the polyester resin at 300°C in the extruder, and extruding the molten material from the filter at a discharge rate of 29.0 g / min. The pressure value at the start of extrusion was taken as the "initial pressure value (MPa)" and the pressure value at the point when extrusion was continued for 12 hours was taken as the "final pressure value (MPa)". The average pressure rise rate was calculated based on these pressure values ​​using the following formula A: Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) A) This is the method used.

[0033] The extruder, filter, and the like used in the above measurements may be any known or commercially available product as long as they satisfy the requirements of the present invention.

[0034] In the present invention, as necessary, as shown in the test examples described later, a reinforcing material may be added to the filter within a range that does not substantially affect the measurement results. In the above measurement method, an extremely high pressure is applied to the filter, so that the filter may be deformed or broken if used alone. In such a case, it is preferable to support the filter with a reinforcing material. As the reinforcing material, a mesh-like metal member or the like can be used. More specifically, a metal filter that has the strength to prevent the filter from being deformed and has a coarse mesh that does not substantially affect the measurement results can be suitably used as the reinforcing material. Then, such a reinforcing material can be used by stacking it on the downstream side of the filter.

[0035] The resin of the present invention is not limited to a particular type as long as it is a polyester resin, but is preferably one mainly made of polyethylene terephthalate (PET). The content of PET in the recycled polyester resin of the present invention is preferably 70% by mass or more, more preferably 80% by mass or more, and more preferably 90 to 100% by mass. Therefore, for example, recycled polyester resins with a PET content of 95 to 99% by mass are also included in the present invention.

[0036] In particular, in the manufacturing method of the present invention described below, PET, which is usually a polycondensation product of ethylene glycol and terephthalic acid, can be obtained, but when components other than ethylene glycol and terephthalic acid are present in the recycled polyester raw material, polyester resins other than PET may be produced by the polycondensation reaction. For this reason, the resin of the present invention may contain, in addition to the main component PET, the following components as acid components or glycol components copolymerized therein. Two or more of these components may be included.

[0037] Examples of the acid component include isophthalic acid, phthalic acid, phthalic anhydride, naphthalenedicarboxylic acid, adipic acid, sebacic acid, 1,4-cyclohexanedicarboxylic acid, dodecanedioic acid, and dimer acid, as well as trimellitic anhydride, trimellitic acid, pyromellitic acid, 1,4-cyclohexanedicarboxylic acid, sebacic acid, and dimer acid.

[0038] Examples of the glycol component include neopentyl glycol, 1,4-butanediol, 1,2-propylene glycol, 1,5-pentanediol, 1,3-propanediol, 1,6-hexamethylenediol, diethylene glycol, 1,4-cyclohexanedimethanol, dimer diol, butylethylpropanediol, (2-methyl-1,3-propanediol, trimethylolpropane, glycerin, pentaerythritol, and ethylene oxide adducts of bisphenol A and bisphenol S.

[0039] 2. Manufacturing method of recycled polyester resin The method for producing the resin of the present invention is not limited, but for example, the resin of the present invention can be suitably produced by the following production method: That is, a method for producing a recycled polyester resin using at least one recycled polyester raw material of a) used polyester products and b) unused polyester generated in the process of producing polyester products, (1) a step of adding the raw material to a mixture containing ethylene terephthalate oligomer and ethylene glycol so that the molar ratio of total glycol components / total acid components is 1.08 to 1.35, and performing depolymerization under heat treatment conditions of 245 to 280° C. to obtain a reaction product containing a depolymerization product (depolymerization step); (2) a step of passing the reaction product through a filter having a filtration particle size of 10 to 25 μm and recovering the filtrate (a filtration step); (3) A step of adding a polymerization catalyst to the filtrate and carrying out a polycondensation reaction of the depolymerization at a temperature of 260° C. or higher and a reduced pressure of 1.0 hPa or lower (polycondensation step). In other words, the recycled polyester resin of the present invention can be suitably obtained by the above-mentioned method for producing a recycled polyester resin.

[0040] Depolymerization process In the depolymerization step, the raw materials are added to a mixture containing ethylene terephthalate oligomer and ethylene glycol so that the molar ratio of total glycol components / total acid components becomes 1.08 to 1.35, and depolymerization is carried out under heat treatment conditions of 245 to 280°C to obtain a reaction product containing a depolymerization product.

[0041] The ethylene terephthalate oligomer and ethylene glycol may be any known or commercially available product, or may be produced by a known production method.

[0042] In particular, as the ethylene terephthalate oligomer, for example, an esterification reaction product of ethylene glycol and terephthalic acid can be suitably used. The number average degree of polymerization of the ethylene terephthalate oligomer is not limited, but can be, for example, about 2 to 20.

[0043] The amount of ethylene terephthalate oligomer used is not particularly limited, but is preferably about 0.20 to 0.80 mass% in 100 mass% of the finally obtained recycled polyester resin, and more preferably 0.30 to 0.70 mass%. If the amount of ethylene terephthalate oligomer is less than the above, the recycled polyester raw materials are likely to block each other when the recycled polyester raw materials are added, and there is a risk of excessive load being applied to the mixer. On the other hand, if the amount of ethylene terephthalate oligomer is more than the above range, there is no particular problem with the depolymerization reaction, but the recycling rate of the finally obtained recycled polyester resin may be low.

[0044] From the viewpoint of allowing the depolymerization reaction to proceed sufficiently, the amount of ethylene glycol added is preferably 5 to 15 parts by mass, more preferably 10 to 15 parts by mass, relative to 100 parts by mass of the ethylene terephthalate oligomer. If the amount of ethylene glycol added exceeds 15 parts by mass, the ethylene terephthalate oligomer tends to solidify in the reactor, and the subsequent reaction may not be able to continue.

[0045] Although there is no particular limitation on the mixing of the ethylene terephthalate oligomer and ethylene glycol, for example, it is preferable to add ethylene glycol to the ethylene terephthalate oligomer. In addition, when adding, it is preferable to make the temperature of the contents uniform while rotating a stirrer in order to prevent the oligomer from solidifying, and then add it.

[0046] To a mixture of ethylene terephthalate oligomer and ethylene glycol, at least one type of recycled polyester raw material is added, which is a) used polyester product and b) unused polyester generated in the process of manufacturing polyester products. Specific examples of the above a) and b) can be the same as those listed in 1. above.

[0047] When the recycled polyester raw material is added, it is preferable to do so under normal pressure while stirring, and more preferable to add it while purging with a small amount of inert gas (generally nitrogen gas is used), which can prevent oxygen from being mixed in and more reliably prevent deterioration of color tone.

[0048] The polyester raw material is added so that the molar ratio of total glycol components / total acid components is 1.08 to 1.35. The molar ratio is particularly preferably 1.10 to 1.33, and more preferably 1.12 to 1.30. If the molar ratio of total glycol components / total acid components is outside the above range, the resulting recycled polyester resin will not satisfy at least one of the carboxyl end group concentration and the diethylene glycol content specified in the present invention, and the average pressure rise rate will also be high. This is because, if the molar ratio of total glycol components / total acid components during the depolymerization reaction is outside the above range, the precipitation of various inorganic substances and foreign substances derived from non-polyester resins is not performed efficiently, so that these foreign substances cannot be effectively filtered in the filtration process, and the foreign substances are likely to precipitate after the polycondensation process, resulting in a recycled polyester resin with a high average pressure rise rate.

[0049] In the production method of the present invention, the depolymerization step is particularly important. That is, in the conventional method using recycled polyester raw materials, depolymerization is performed using only recycled polyester raw materials, whereas in the present invention, the depolymerization reaction of the recycled polyester raw materials is performed in the presence of ethylene terephthalate oligomers and ethylene glycol, and the recycled polyester raw materials are charged so that the molar ratio of the total glycol components / total acid components of all the components of the oligomer, ethylene glycol, and recycled polyester raw materials is within the above range, and the depolymerization reaction is performed. In this way, not only various inorganic substances but also foreign substances derived from non-polyester resins are efficiently precipitated, so that these foreign substances can be effectively filtered in the filtration step described below. Then, in the polycondensation step described below, it is possible to obtain a recycled polyester resin in which the diethylene glycol content and the carboxyl terminal group concentration are below a specific amount and the amount of foreign substances mixed in is relatively small. Note that, in the production method of the present invention, it is desirable that the recycled polyester raw materials are not decomposed into monomers by the above depolymerization reaction, but are decomposed into oligomers having about 5 to 20 repeating units. By controlling in this manner, not only various inorganic substances but also foreign substances derived from non-polyester resins are efficiently precipitated, so that it is possible to remove a larger amount of foreign substances.

[0050] In the depolymerization step, the reaction temperature during depolymerization (particularly the internal temperature of the reactor) is preferably set in the range of 245 to 280°C, and more preferably in the range of 255 to 275°C. If the reaction temperature during depolymerization is less than 245°C, the reaction product solidifies, the operability deteriorates, and even if a recycled polyester resin is obtained, the diethylene glycol content or the carboxyl terminal group concentration tends to be too high. If the reaction temperature exceeds 280°C, the diethylene glycol content or the carboxyl terminal group concentration of the obtained recycled polyester resin may be too high.

[0051] The reaction time for depolymerization (the reaction time from the end of the feeding of the recycled polyester raw material) is not particularly limited, but is usually preferably within 4 hours, and more preferably within 2 hours, from the viewpoints of suppressing the amount of diethylene glycol by-produced and suppressing deterioration of the color tone of the polyester, etc. The lower limit of the reaction time is not limited, and can be, for example, about 1 hour.

[0052] The reaction apparatus used in the production method of the present invention is not particularly limited, and known or commercially available apparatuses can be used. In particular, the volume, shape of the stirring blades, etc. of the reaction apparatus may be a generally used esterification reaction apparatus without any problem, but in order to efficiently advance the depolymerization reaction, it is preferable to use a reaction apparatus having a structure in which a distillation column is attached so as not to distill ethylene glycol out of the system.

[0053] Filtration process In the filtration step, the reaction product is passed through a filter having a filtration grain size of 10 to 25 μm to recover the filtrate.

[0054] The reaction product obtained in the depolymerization step is a liquid containing mainly depolymerized polyester raw material. In the filtration step, the liquid is passed through a filter having a filtration particle size of 10 to 25 μm to filter out foreign matter, and the filtrate is collected. In the depolymerization step, not only various inorganic substances but also foreign matter derived from non-polyester resins is efficiently precipitated, so that by passing through a filter having a filtration particle size of 10 to 25 μm, the precipitated foreign matter can be filtered out, and a depolymer containing less foreign matter can be obtained. If a filter having a filtration particle size of more than 25 μm is used, foreign matter in the polymer cannot be sufficiently removed, and the amount of foreign matter in the obtained recycled polyester resin increases. For this reason, when such a resin is used for spinning, pressure rise of the nozzle pack or thread breakage occurs. On the other hand, if a filter having a filtration particle size of less than 10 μm is used, clogging due to foreign matter is likely to occur, and the filter life is shortened, which is disadvantageous in terms of cost and may also reduce operability.

[0055] The filter that can be used in the filtration step can be a general filter without any problem, but a metal filter is particularly preferable. Examples of the material include stainless steel. The filter type is also not particularly limited, and examples include a screen changer type filter, a leaf disk filter, and a candle type sintered filter. These can be publicly known or commercially available filters.

[0056] Polycondensation process In the polycondensation step, a polycondensation catalyst is added to the filtrate, and the depolymerization is carried out at a temperature of 260° C. or higher and under a reduced pressure of 1.0 hPa or lower.

[0057] The polycondensation catalyst is not limited, but may be at least one of germanium compounds, antimony compounds, titanium compounds, cobalt compounds, etc. Among them, at least one of germanium compounds and antimony compounds is particularly used. When the transparency of the resulting recycled polyester resin is important, it is preferable to use a germanium compound. Examples of the above compounds include oxides, inorganic acid salts, organic acid salts, halides, sulfides, etc. of germanium, antimony, titanium, cobalt, etc.

[0058] The amount of the polycondensation catalyst used is not particularly limited, but for example, it is 5 × 10 -5 It is preferable to have a concentration of 6×10 moles / unit or more. -5 The upper limit of the amount used is, for example, 1×10 -3 It can be about mole / unit, but is not limited to this.

[0059] In addition, since the polymerization catalyst contained in the recycled polyester raw material may also act as a catalyst during the polycondensation reaction, it is preferable to take into consideration the type and content of the polymerization catalyst contained in the recycled polyester raw material when adding a polymerization catalyst in the polycondensation step.

[0060] During the polycondensation reaction, if necessary, a fatty acid ester capable of adjusting the melt viscosity, a hindered phenol-based antioxidant, or a phosphorus compound capable of suppressing thermal decomposition of the resin can be added together with the above-mentioned polycondensation catalyst.

[0061] Examples of fatty acid esters include beeswax (a mixture mainly composed of myricyl palmitate), stearyl stearate, behenyl behenate, stearyl behenate, glycerin monopalmitate, glycerin monostearate, glycerin distearate, glycerin tristearate, pentaerythritol monopalmitate, pentaerythritol monostearate, pentaerythritol distearate, pentaerythritol tristearate, pentaerythritol tetrastearate, dipentaerythritol hexastearate, etc. Among these, glycerin monostearate, pentaerythritol tetrastearate, and dipentaerythritol hexastearate are preferred. These can be used alone or in combination of two or more.

[0062] Examples of the hindered phenol antioxidants include 2,6-di-t-butyl-4-methylphenol, n-octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane, tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, 4,4'-butylidenebis-(3-methyl-6-t-butylphenol), tris(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, ... Ethylene glycol-bis[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionate], 3,9-bis{2-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy]-1,1'-dimethylethyl}-2,4,8,10-tetraoxaspiro[5,5]undecane, etc. are used, but tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane is preferred in terms of effectiveness and cost. These can be used alone or in combination of two or more.

[0063] Examples of phosphorus compounds that can be used include phosphorous acid, phosphoric acid, trimethyl phosphite, triphenyl phosphite, tridecyl phosphite, trimethyl phosphate, tridecyl phosphate, triphenyl phosphate, etc. These compounds can be used alone or in combination of two or more.

[0064] In the polycondensation reaction, the polycondensation reaction is carried out at a temperature of 260°C or higher and under reduced pressure of 1.0 hPa or lower. If the polycondensation reaction temperature is lower than 260°C or the pressure during the polycondensation reaction exceeds 1.0 hPa, the polycondensation reaction time is long, resulting in poor productivity. It is more preferable that the polycondensation reaction temperature is 270°C or higher. However, if the polycondensation reaction temperature is too high, the polymer will be colored due to thermal decomposition, the color tone will deteriorate, and the amount of terminal groups (COOH) will also increase due to thermal decomposition. For this reason, in the present invention, the upper limit of the polycondensation reaction temperature is generally preferably 285°C or lower.

[0065] The intrinsic viscosity of the recycled polyester resin of the present invention obtained by the above polycondensation reaction is not particularly limited, but is usually preferably about 0.44 to 0.80. In addition, the recycled polyester resin of the present invention can also be used for molding purposes by being highly polymerized through a solid-phase polymerization process as described below. In this case, the intrinsic viscosity of the obtained recycled polyester resin is preferably 0.80 to 1.25.

[0066] Crystallization process In the present invention, the polyester resin obtained above can be further subjected to a crystallization step, if necessary, to enhance the crystallinity of the polyester resin.

[0067] The crystallization conditions are not particularly limited, but can be carried out, for example, by heat treatment at the crystallization temperature of the polyester resin used or a temperature higher than that. For example, when the polyester resin is PET, since the crystallization temperature of PET is usually about 130° C., the heat treatment can be carried out at a temperature of, for example, 135° C. or higher (preferably 140 to 180° C.). The heat treatment time can be changed depending on the heat treatment temperature, etc., and can be, for example, about 30 minutes to 20 hours, but is not limited thereto.

[0068] Solid phase polymerization process In the present invention, if necessary, the resin obtained in the polycondensation step or the crystallization step can be further subjected to a solid-state polymerization reaction, whereby the recycled polyester resin can be further polymerized to a high degree, thereby making the physical properties more suitable for molding.

[0069] The conditions for the solid-state polymerization reaction are not limited, but it is preferable to carry out the heat treatment so that the intrinsic viscosity of the resulting recycled polyester resin is 0.80 to 1.25 (particularly 0.82 to 1.24). More specifically, for example, the heat treatment can be carried out by heat treating the resin obtained in the polycondensation step or crystallization step in an inert gas atmosphere at about 180 to 240°C. The heat treatment time depends on the heat treatment temperature, etc., but is usually about 5 to 50 hours.

[0070] 3. Use of recycled polyester resin The resin of the present invention can be used for the production of various products as it is or after being mixed with other additives as necessary to form a resin composition.

[0071] Examples of the additives include, in addition to the above-mentioned additives such as polymerization catalysts, antioxidants, and phosphorus compounds, colorants, pigments, dispersants, fillers, ultraviolet absorbers, thickeners, antistatic agents, coloring inhibitors, stabilizers, flame retardants, lubricants, and the like, so long as the additives do not impair the effects of the present invention.

[0072] In particular, a coloring inhibitor can be suitably used. For example, phosphorus compounds such as phosphorous acid, phosphoric acid, trimethyl phosphite, triphenyl phosphite, tridecyl phosphite, trimethyl phosphate, tridecyl phosphate, and triphenyl phosphate can be used. These phosphorus compounds may be used alone or in combination of two or more kinds.

[0073] In order to suppress coloration due to thermal decomposition of the polyester resin, additives such as cobalt compounds such as cobalt acetate, manganese compounds such as manganese acetate, anthraquinone dye compounds, and copper phthalocyanine compounds may be contained.

[0074] The various products can be in the same form as conventional polyester products, and can be suitably used in the form of, for example, fibers, molded articles, films, etc.

[0075] In the case of fibers, for example, the fibers can be produced by a production method including a step of melting and spinning a raw material containing the resin of the present invention. This makes it possible to produce ultrafine fibers having a single fiber fineness of, for example, 0.8 decitex or less (preferably 0.6 to 0.3 decitex). The spinning method and the like can be carried out according to known conditions.

[0076] As described above, the resin of the present invention has a relatively low content of foreign matter and has properties equivalent to those of virgin polyester resin, and therefore, troubles such as yarn breakage are unlikely to occur in any of the melt spinning, drawing / heat treatment and winding steps, and polyester fibers can be obtained with good productivity.

[0077] The fiber of the present invention containing the resin of the present invention may be, for example, either a monofilament or a multifilament, and may be either a long fiber or a short fiber. In fiber production, it is generally more difficult to produce a multifilament, but the fiber of the present invention can be a multifilament having, for example, a single yarn fineness of 0.3 to 30 decitex, a single yarn number of 2 to 300, a total fineness of 5 to 350, a strength of 1 to 5 cN / decitex, and an elongation of 10 to 400%. Among them, it is also possible to obtain ultrafine fibers, which are more difficult to produce.

[0078] In the case of molded products, for example, the resin of the present invention can be produced by applying various molding methods such as press molding, extrusion molding, compressed air molding, and blow molding using a raw material containing the resin of the present invention. This makes it possible to provide various parts, including containers. The resin of the present invention is particularly suitable for producing blow molded products because it has properties similar to those of virgin polyester resin and has excellent thermal stability. Therefore, a method for producing a molded product, which includes a step of obtaining a parison from a melt containing the resin of the present invention and a step of blowing gas into the parison, can be suitably adopted. This makes it possible to produce molded products such as containers.

[0079] In the case of a film, a raw material containing the resin of the present invention can be molded by a known film-forming method. For example, the melt of the raw material is extruded from a T-die and then cooled with a casting roll to produce an unstretched sheet. The resin of the present invention has a relatively low content of foreign matter and excellent thermal stability, so that stretching in the MD and TD directions can be performed with good operability. The stretching method may be either uniaxial stretching or biaxial stretching, and the biaxial stretching method may be either simultaneous biaxial stretching or sequential biaxial stretching. Then, a polyester film having properties such as strength and elongation almost the same as those when virgin polyester resin is used and excellent in transparency can be obtained.

[0080] The thickness of the film is not limited, but can be set appropriately within the range of 10 to 50 μm. If necessary, the film can be laminated with other layers (e.g., an adhesive layer, a heat seal layer, a surface protection layer, a print layer, a design layer, etc.) to be used as a laminate, and the laminate can be molded to be used as various molded products as described above. EXAMPLES

[0081] The features of the present invention will be described in more detail below with reference to examples and comparative examples, although the scope of the present invention is not limited to the examples.

[0082] A. About recycled polyester resin Example 1 A slurry of terephthalic acid (TPA) and ethylene glycol (EG) (TPA / EG molar ratio = 1 / 1.6) was supplied to an esterification reactor and reacted at a temperature of 250°C and a pressure of 50 hPa to obtain ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95%. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the esterification reactor, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the esterification reactor was rotating. When the internal temperature of the esterification reactor (hereinafter referred to as the "ES can") stopped decreasing, 55.0 parts by mass of recycled polyester raw material (pellet-like polyester waste generated in the process of manufacturing polyester resin) was added in a fixed amount via a rotary valve over a period of about 2 hours. At this time, the recycled polyester raw material was charged so that the molar ratio of total glycol components / total acid components (hereinafter sometimes referred to as "G / A") was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. Then, the obtained depolymerization product was pressure-fed to a polycondensation reactor (hereinafter referred to as PC can) through a candle filter with a mesh size of 20 μm set between the esterification reactor and the polycondensation reactor, and then 1.0×10 antimony trioxide was added as a polymerization catalyst. -4mol / unit, EG slurry of titanium dioxide was added to make the concentration 0.20 mass%, and the PC can was decompressed and after 60 minutes, a melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0083] Example 2 An ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained in the same manner as in Example 1. 45.0 parts by mass of the ethylene terephthalate oligomer was charged into an ES can, and then 7.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester raw material (PET bottles crushed or remelted and pelletized) was added at a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material was charged so that the G / A was 1.16. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was then pressure-fed into the PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and antimony trioxide was added as a polymerization catalyst at a rate of 1.0×10 -4 mol / unit, EG slurry of titanium dioxide was added to make the concentration 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0084] Example 3 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 55.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 15.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 45.0 parts by mass of recycled polyester raw material (same as in Example 1) was added in a fixed amount via a rotary valve over about 2 hours. At this time, the recycled polyester raw material was charged so that the G / A was 1.33. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was then pressure-fed into the PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and antimony trioxide was added as a polymerization catalyst at a rate of 1.0×10 -4 The mixture was added so as to obtain a ratio of mol / unit, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 2 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.46).

[0085] Example 4 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 30.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 7.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 70.0 parts by mass of recycled polyester raw material (same as in Example 1) was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material was charged so that the G / A was 1.10. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was then pressure-fed into the PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and antimony trioxide was added as a polymerization catalyst at a rate of 1.0×10 -4 The mixture was added so as to obtain a ratio of mol / unit, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 5 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.65).

[0086] Example 5 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into an ES can, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester raw material (same as in Example 1) was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material was charged so that the G / A was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 250°C. The obtained depolymerized polymer was then pressure-fed into the PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and antimony trioxide was added as a polymerization catalyst at a rate of 1.0×10 -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make the concentration 0.30 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 280°C for 6 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.82).

[0087] Example 6 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was pressure-fed into a PC can through a candle filter with a mesh size of 25 μm set between the ES can and the PC can, and then 1.0 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4mol / unit, EG slurry of titanium dioxide was added to make 0.05 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 280°C for 3 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.56).

[0088] Example 7 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was then pressure-fed into a PC can through a candle filter with a mesh size of 15μm set between the ES can and the PC can, and 1.0×10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added so as to be 0.05 mass%, and the PC can was decompressed and after 60 minutes, the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 280°C for 2 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.50).

[0089] Example 8 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was then pressure-fed into a PC can through a candle filter with a mesh size of 10 μm set between the ES can and the PC can, and antimony trioxide was added at 1.0 × 10 as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make 0.05 mass%, and the PC can was decompressed and after 60 minutes, the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 280°C for 5 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.75).

[0090] Example 9 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was pressure-fed into a PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and then 1.0 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4mol / unit, EG slurry of titanium dioxide was added to make 0.05 mass%, and the PC can was decompressed and after 60 minutes, the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 260°C for 7 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.61).

[0091] Comparative Example 1 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 30.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 2.5 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 70.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.06. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was pressure-fed into a PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and then 1.0 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make the concentration 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0092] Comparative Example 2 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 50.0 parts by mass of ethylene terephthalate oligomer was charged into an ES can, and then 19.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 50.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, recycled polyester raw material (same as in Example 1) was added so that G / A was 1.36. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was pressure-fed into a PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and then 1.0 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make the concentration 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0093] Comparative Example 3 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 7.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.16. Then, the depolymerization reaction was carried out under heat treatment conditions at 290°C for 1 hour. The obtained depolymerized polymer was then pressure-fed into a PC can through a candle filter with a mesh size of 20 μm that was set between the ES can and the PC can, and 1.0 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4mol / unit, EG slurry of titanium dioxide was added to make the concentration 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0094] Comparative Example 4 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 10.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester raw material was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material (same as in Example 1) was added so that the G / A was 1.20. Then, the depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. The obtained depolymerized polymer was then pressure-fed into a PC can through a candle filter with a mesh size of 30 μm set between the ES can and the PC can, and 0.7 × 10 antimony trioxide was added as a polymerization catalyst. -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make the concentration 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0095] Comparative Example 5 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 48.8 parts by mass of recycled polyester raw material (same as in Example 1) was charged into an ES can, followed by 19.2 parts by mass of ethylene glycol, and depolymerization reaction was carried out for 4 hours under heat treatment conditions at 250° C. The molar ratio of total glycol components / total acid components during this depolymerization reaction was 1.59. The obtained depolymerization product was pressure-fed into a PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and then 51.2 parts by mass of ethylene terephthalate oligomer was charged into the PC can and mixed with the depolymerization product. At this time, the recycled polyester raw material was charged so that the G / A was 1.37. Then, antimony trioxide was added as a polymerization catalyst at 1.0 × 10 -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, EG slurry of titanium dioxide was added to make the concentration 0.40 mass%, and the PC can was decompressed for 60 minutes, after which the melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 275°C for 4 hours to obtain a recycled polyester resin (intrinsic viscosity: 0.64).

[0096] Comparative Example 6 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 7.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester was added in a fixed amount via a rotary valve over a period of about 2 hours, but the contents solidified in the reactor, making it impossible to continue the reaction thereafter.

[0097] Comparative Example 7 In the same manner as in Example 1, an ethylene terephthalate oligomer (number average degree of polymerization: 5) with an esterification reaction rate of 95% was obtained. 45.0 parts by mass of ethylene terephthalate oligomer was charged into the ES can, and then 7.0 parts by mass of ethylene glycol was added while the agitator of the ES can was rotating. When the internal temperature of the ES can stopped decreasing, 55.0 parts by mass of recycled polyester raw material (similar to that in Example 1) was added in a fixed amount over about 2 hours via a rotary valve. At this time, the recycled polyester raw material was added so that the G / A was 1.16. Thereafter, a depolymerization reaction was carried out for 1 hour under heat treatment conditions at 270°C. Then, the obtained depolymerized polymer was pressure-fed into the PC can through a candle filter with a mesh size of 20 μm set between the ES can and the PC can, and antimony trioxide was added as a polymerization catalyst at a rate of 1.0×10 -4 mol / unit, cobalt acetate 0.5×10 -4 mol / unit, and EG slurry of titanium dioxide was added to make the concentration 0.40 mass%, and the PC can was depressurized and after 60 minutes, a melt polymerization reaction was carried out at a final pressure of 0.5 hPa and a temperature of 255°C, but no recycled polyester resin was obtained.

[0098] Test Example 1 The following properties were examined for each of the recycled polyester resins obtained in Examples 1 to 9 and Comparative Examples 1 to 7. The results are shown in Table 1. The measurement or evaluation of each property value was carried out as follows.

[0099] (a) Intrinsic viscosity The resulting recycled polyester resin is used, and measurements are made at 20°C using an equal mass mixture of phenol and tetrachloroethane as the solvent.

[0100] (b) Composition of polyester resin The obtained polyester resin was dissolved in a mixed solvent of deuterated hexafluoroisopropanol and deuterated chloroform in a volume ratio of 1:20, and 1H-NMR was measured using a JEOL "LA-400 NMR" apparatus. The type and content of copolymerization components were determined from the integrated intensity of the proton peak of each component in the obtained chart.

[0101] (c) Carboxyl end group concentration 0.1 g of the resulting recycled polyester resin was dissolved in 10 ml of benzyl alcohol, and 10 ml of chloroform was added to the solution, which was then titrated with a 1 / 10 N solution of potassium hydroxide in benzyl alcohol to determine the content.

[0102] (d) Average boost rate measured by a boost test machine The polyester resin was melted at 300°C in an extruder, and a stainless steel twill weave filter (nominal mesh size: 1400 mesh, weaving method: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical wire diameter: 0.07 mm, horizontal wire diameter: 0.04 mm, filtration grain size: 12 μm, viscous resistance coefficient (m -1 ):2.60×10 7 A filter (stainless steel plain weave wire mesh (nominal mesh size: 40 mesh, weave: plain weave, wire diameter: 0.21 mm, manufactured by Kamijo Seiki Co., Ltd.) is set on the back side (downstream side) of the filter, and a reinforcing material (stainless steel plain weave wire mesh (nominal mesh size: 40 mesh, weave: plain weave, wire diameter: 0.21 mm, manufactured by Kamijo Seiki Co., Ltd.) is layered on the back side (downstream side). The polymer discharge rate is set to 29.0 g / min, and the filter pressure is measured using a pressure rise tester (Asahi Gauge Co., Ltd. "MES-Y44D type" detector). A pressure rise test using the pressure rise tester is performed continuously for 12 hours, and the average pressure rise rate is calculated using the following formula from the initial pressure value (MPa) at the start of the pressure rise test (the minimum pressure value between 5 and 10 minutes after the polyester resin begins to pass through the filter is defined as the initial pressure) and the final pressure value (MPa) after 12 hours have passed. Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12

[0103] [Table 1]

[0104] As is clear from the results in Table 1, the recycled polyester resins obtained in Examples 1 to 9 had excellent spinning operability because the amount of carboxyl terminal groups, the diethylene glycol content, and the average pressure rise rate were within the ranges specified in the present invention. On the other hand, in Comparative Example 1, since the G / A during the depolymerization reaction was low, the obtained recycled polyester resin had a high carboxyl end group concentration and a high average pressure increase rate. In Comparative Example 2, since the G / A during the depolymerization reaction was high, the obtained recycled polyester resin had a high diethylene glycol content and a high average pressure increase rate. In Comparative Example 3, the depolymerization step was carried out under heat treatment conditions at 290° C., so the obtained recycled polyester resin had a high carboxyl terminal group concentration and a high diethylene glycol content. In Comparative Example 4, the filtration particle size of the candle filter provided between the ES can and the PC can was 30 μm, so the average pressure rise rate of the obtained recycled polyester resin was high. In Comparative Example 5, the production method of the present invention was not performed, and the G / A during the depolymerization reaction was high, so the obtained recycled polyester resin had a high diethylene glycol content and a high average pressure increase rate. In Comparative Example 6, the depolymerization step was carried out under heat treatment conditions at 230° C., so that the contents in the reactor solidified, making it impossible to continue the reaction thereafter. In Comparative Example 7, since the polycondensation reaction temperature in the polycondensation step was 255° C., the polymerization rate was slow and a recycled polyester resin could not be obtained.

[0105] B. Fibers made from recycled polyester resin Example 10 The recycled polyester resin obtained in Example 1 was spun by an extruder-type melt spinning machine from a spinning nozzle (hole diameter 0.15 mm, number of holes 84) equipped with a filter having a filtration particle size of 20 μm at a resin temperature of 295° C., and wound up at a spinning speed of 2900 m / min. The obtained undrawn yarn was drawn in a drawing device at a drawing temperature of 160° C. and a draw ratio of 1.5 times to obtain a drawn multifilament yarn having a fineness of 35 dtex.

[0106] Example 11 Spinning and drawing were carried out in the same manner as in Example 10, except that the recycled polyester resin obtained in Example 4 was used, to obtain a drawn multifilament yarn.

[0107] Example 12 The recycled polyester resin obtained in Example 1 was spun by an extruder-type melt spinning machine from a spinning nozzle (hole diameter 0.2 mm, number of holes 72 holes) equipped with a filter having a filtration particle size of 15 μm at a resin temperature of 301° C., and wound up at a spinning speed of 3250 m / min. The obtained undrawn yarn was drawn in a drawing device at a drawing temperature of 160° C. and a draw ratio of 1.6 times to obtain a drawn multifilament yarn having a fineness of 84 dtex.

[0108] Example 13 Spinning and drawing were carried out in the same manner as in Example 12, except that the recycled polyester resin obtained in Example 4 was used, to obtain a drawn multifilament yarn.

[0109] Comparative Example 8 Spinning and drawing were performed in the same manner as in Example 10, except that the recycled polyester resin obtained in Comparative Example 1 was used. However, the pressure rise during spinning was so rapid that many broken yarns occurred, making it impossible to obtain an undrawn yarn.

[0110] Comparative Example 9 Spinning and drawing were carried out in the same manner as in Example 10, except that the recycled polyester resin obtained in Comparative Example 2 was used, to obtain a drawn multifilament yarn.

[0111] Test Example 2 The strength, elongation, number of fluff, and runnability (yarn breakage, pressure rise) of the drawn multifilament yarns obtained in Examples 10 to 13 and Comparative Example 9 were examined. The results are shown in Table 2. The strength, elongation, number of fluff, and runnability (yarn breakage, pressure rise) were measured or evaluated as follows.

[0112] (e) Strength and elongation Measurements were performed using a Tensilon RTC-1210 (manufactured by Orientec Co., Ltd.) in accordance with JIS L1013.

[0113] (f) Number of fuzz Using drawn yarn, the number of fluffs (pieces / 10 8 The fiber length (m) was measured. 8 I went at m.

[0114] (g) Operational efficiency (yarn cutting, pressure increase) Broken yarn: The number of broken yarns during 24 hours of continuous spinning was counted, and 3 or less times / 24 hours was marked as "○", and 4 or more times / 24 hours was marked as "×". Pressure increase: Spinning was performed continuously for 24 hours, and the nozzle pack pressure was measured during that time. If the pressure did not increase by 2 MPa or more from the pressure set at the beginning of spinning, it was marked as "O", and if such a pressure increase occurred, it was marked as "X".

[0115] [Table 2]

[0116] As is clear from Table 2, in Examples 10 to 13, multifilament yarns could be obtained with good spinning operability using recycled polyester resin, and the obtained multifilament yarns had good yarn properties and were practically problem-free fibers. In particular, in Examples 10 and 11, ultrafine multifilaments with single fiber fineness of 0.5 decitex or less could be produced with good spinning operability. On the other hand, in Comparative Example 8, since the recycled polyester resin obtained in Comparative Example 1 was used, the pressure rise during spinning was intense, and many yarn breaks occurred, so that an undrawn yarn could not be obtained. In Comparative Example 9, although a drawn multifilament yarn could be obtained, it had low strength and low elongation, and also generated a lot of fluff, which was problematic in practical use.

[0117] C. Molded products using recycled polyester resin Example 14 The recycled polyester resin (intrinsic viscosity 0.64) obtained in Example 1 was continuously fed to a crystallizer and crystallized at 150°C. Then, it was fed to a dryer and dried at 175°C for 4 hours. It was then sent to a preheater and heated to 210°C. It was then fed to a solid-state polymerization reactor and subjected to a solid-state polymerization reaction at 210°C for 30 hours in a nitrogen gas atmosphere to obtain a recycled polyester resin with an intrinsic viscosity of 1.21. The recycled polyester resin obtained by the solid-state polymerization reaction was chipped and dried, and then the resin was extruded at an extrusion temperature of 280°C using a direct blow molding machine (manufactured by Tahara) to form a cylindrical parison, which was then sandwiched between metal molds while still in a softened state, the bottom was formed, and the bottle was then blown to form a bottle. At this time, the bottom was formed when the parison had a diameter of 3 cm and a length of 25 cm, and a 350 ml hollow container (direct blow molding product) was obtained by blow molding.

[0118] Example 15 A solid-state polymerization reaction was carried out in the same manner as in Example 14, except that the recycled polyester resin obtained in Example 4 was used, to obtain a recycled polyester resin having an intrinsic viscosity of 1.15. The recycled polyester resin obtained by the solid-state polymerization reaction was used to carry out direct blow molding in the same manner as in Example 14 to obtain a hollow container.

[0119] Comparative Example 10 A solid-state polymerization reaction was carried out in the same manner as in Example 14, except that the recycled polyester resin obtained in Comparative Example 1 was used, to obtain a recycled polyester resin having an intrinsic viscosity of 1.18. The recycled polyester resin obtained by the solid-state polymerization reaction was used to carry out direct blow molding in the same manner as in Example 14 to obtain a hollow container.

[0120] Comparative Example 11 A solid-state polymerization reaction was carried out in the same manner as in Example 14, except that the recycled polyester resin obtained in Comparative Example 2 was used, to obtain a recycled polyester resin having an intrinsic viscosity of 1.20. The recycled polyester resin obtained by the solid-state polymerization reaction was used to carry out direct blow molding in the same manner as in Example 14 to obtain a hollow container.

[0121] Test Example 3 The evaluation results of moldability, haze and impact resistance of the hollow containers obtained in Examples 14 to 15 and Comparative Examples 10 to 11 are shown in Table 3. The evaluation or measurement of moldability, haze and impact resistance was carried out as follows.

[0122] (h) Formability The thickness of the body of the resulting containers (100 samples) was measured, and samples with a difference in thickness between the thickest and thinnest parts of up to 0.30 mm were deemed to pass, and the number of passing samples was shown.

[0123] (i) Haze Sample pieces (20 pieces) were cut out from the obtained container, and the turbidity was measured using a turbidity meter Model 1001DP manufactured by Nippon Denshoku Industries Co., Ltd. (air: haze 0%), and the average value was calculated for n=20. The smaller this value, the better the transparency, and a value of 6% or less was judged to be excellent transparency.

[0124] (j) Impact resistance Molded articles that passed the moldability evaluation in (h) above (100 samples) were filled with 340 ml of tap water and dropped once on a P tile from a height of 200 cm with the bottom surface facing down and once with the side surface facing down at room temperature. If 90 or more molded articles did not break, the impact resistance was evaluated as good.

[0125] [Table 3]

[0126] As is clear from the results in Table 3, the hollow containers obtained in Examples 14 to 15 were easily molded, and the obtained hollow containers had low haze, excellent transparency, and excellent impact resistance. On the other hand, in Comparative Example 10, a recycled polyester resin having a high concentration of carboxyl terminal groups was used, and therefore the moldability was poor, and the obtained hollow container was poor in both transparency and impact resistance. In Comparative Example 11, a recycled polyester resin with a high diethylene glycol content was used, which resulted in poor moldability, and the obtained hollow container was poor in both transparency and impact resistance.

[0127] D. Films made from recycled polyester resin Example 16 93.5% by mass of the recycled polyester resin (intrinsic viscosity 0.64) obtained in Example 1 and 6.5% by mass of polyethylene terephthalate resin containing 1.5% by mass of silica particles were mixed as master chips, and both resins were melt-kneaded in an extruder, fed to a T-die and discharged in a sheet shape, wound around a metal drum whose temperature was adjusted to 20 ° C, cooled and wound up to produce an unstretched sheet with a thickness of about 150 μm. Next, the end of this unstretched sheet was held with a clip of a tenter-type simultaneous biaxial stretching device, and simultaneously biaxially stretched at a stretch ratio of 3.0 times in the MD direction and 3.3 times in the TD direction under the condition of 180 ° C, and then heat-treated at 215 ° C for 4 seconds with a relaxation rate of 5% in the TD direction, slowly cooled to room temperature, and wound up after corona discharge treatment on one side. In this way, a biaxially stretched PET resin film with a thickness of 15 μm was obtained. The recycling ratio in this film was 51.4%.

[0128] Example 17 An unstretched sheet was produced in the same manner as in Example 16, except that the recycled polyester resin obtained in Example 4 was used instead of the recycled polyester resin obtained in Example 1. A stretching heat treatment was then performed in the same manner as in Example 16 to obtain a biaxially stretched PET resin film having a thickness of 15 μm.

[0129] Comparative Example 12 An attempt was made to produce an unstretched sheet in the same manner as in Example 16, except that the recycled polyester resin obtained in Comparative Example 1 was used instead of the recycled polyester resin obtained in Example 1. However, due to contamination of the lip surface of the T-die, film breakage, roll contamination, etc., production was no longer possible within 2 hours of the start of operation, and the unstretched sheet could not be subjected to the stretching process, and a biaxially stretched PET resin film could not be obtained.

[0130] Comparative Example 13 An unstretched sheet was produced in the same manner as in Example 16, except that the recycled polyester resin obtained in Comparative Example 2 was used instead of the recycled polyester resin obtained in Example 1, and a stretching heat treatment was performed in the same manner as in Example 16 to obtain a biaxially stretched PET resin film having a thickness of 12 μm. However, for the same reason as in Comparative Example 12, continuous operation for 24 hours or more was not possible, and production was not possible in 14 hours.

[0131] Test Example 4 Table 4 shows the property values ​​and the evaluation results of runnability of the biaxially stretched PET resin films obtained in Examples 16 to 17 and Comparative Example 13. The tensile strength, haze, and runnability were evaluated or measured as follows.

[0132] (k) Tensile strength (MPa) The tensile strength was measured in accordance with JIS K7127 using a Shimadzu DSS-500 Autograph. The biaxially stretched PET resin films obtained in the Examples and Comparative Examples were cut out from the center in the TD direction to a width of 10 mm and a length of 150 mm in the MD direction and TD direction, respectively, to prepare samples. The measurement was performed under the conditions of a measurement length of 100 mm and a pulling speed of 500 mm / min, and the tensile strength was calculated using the following formula. Tensile strength (MPa) = tensile load at break (N) / average original cross-sectional area of ​​the measured sample (mm 2 )

[0133] (l) Haze (%) The central portion in the TD direction of the biaxially stretched PET resin film obtained in each of the Examples and Comparative Examples was measured using a haze meter (NDH4000) manufactured by Nippon Denshoku Industries Co., Ltd., in accordance with JIS K7136.

[0134] (m) Operational feasibility The polyester film was continuously produced and evaluated according to the following criteria. ○: Operation was possible for more than 24 hours continuously. ×: During 24-hour continuous operation, the film could not be produced due to contamination of the lip surface of the T-die, film breakage, roll contamination, etc.

[0135] [Table 4]

[0136] As is clear from the results in Table 4, the biaxially stretched PET resin films obtained in Examples 16 and 17 had high tensile strength in both MD and TD directions, low haze, and excellent transparency, and had properties comparable to those of a film made of virgin polyester resin. Furthermore, the operability was also good. On the other hand, in Comparative Example 12, a recycled polyester resin having a high carboxyl end group concentration and a high average pressure increase rate was used, so that the operability was poor and a biaxially stretched PET resin film could not be obtained. In Comparative Example 13, a recycled polyester resin having a high diethylene glycol content was used, which resulted in poor operability, and the obtained biaxially stretched PET resin film was poor in both tensile strength and transparency.

Claims

1. A polyester resin comprising a component derived from at least one recycled polyester raw material, which is selected from a) used polyester products and b) unused polyester resins generated in a process for producing polyester products, (1) When the total amount of all glycol components is 100 mol %, the content of diethylene glycol is 4 mol % or less, (2) The carboxyl end group concentration is 30 equivalents / t or less, (3) The average pressure rise rate is 0.6 MPa / h or less (wherein the average pressure rise rate is a value calculated by the following procedure: a pressure rise tester including an extruder and a pressure sensor is used, a stainless steel filter (nominal mesh size: 1400 mesh, weave: twill weave, vertical mesh: 165 mesh, horizontal mesh: 1400 mesh, vertical line diameter: 0.07 mm, horizontal line diameter: 0.04 mm, filtration particle size: 12 μm) is set at the tip of the extruder, polyester resin is melted at 300° C. in the extruder, and the melt is extruded from the filter at a discharge rate of 29.0 g / min. The pressure value at the start of extrusion is defined as the "initial pressure value (MPa)", and the pressure value at the time of extrusion for 12 hours thereafter is defined as the "final pressure value (MPa)". Based on these pressure values, the average pressure rise rate is calculated by the following calculation formula A: Average pressure rise rate (MPa / h) = (final pressure value - initial pressure value) / 12) ... A), A recycled polyester resin.

2. A fiber comprising the recycled polyester resin according to claim 1.

3. A blow molded article comprising the recycled polyester resin according to claim 1.

4. A film comprising the recycled polyester resin according to claim 1.

5. A method for producing a recycled polyester resin using at least one recycled polyester raw material, which is a) a used polyester product and b) an unused polyester generated in a process for producing a polyester product, comprising: (1) a step of adding the raw material to a mixture containing ethylene terephthalate oligomer and ethylene glycol so that the molar ratio of total glycol components / total acid components becomes 1.08 to 1.35, and performing depolymerization under heat treatment conditions of 245 to 280° C. to obtain a reaction product containing a depolymerization product; (2) passing the reaction product through a filter having a filtration particle size of 10 to 25 μm to recover a filtrate; (3) A step of adding a polymerization catalyst to the filtrate and carrying out a polycondensation reaction of the depolymerization at a temperature of 260° C. or higher and a reduced pressure of 1.0 hPa or lower. A method for producing a recycled polyester resin, comprising:

6. The method according to claim 5, wherein the raw material contains at least one of a) used polyester products and b) unused polyester resins generated in a process for producing polyester products in an amount of 40% by mass or more.

Citation Information

Patent Citations

  • Chemical recycle of polyethylene terephthalate waste

    JP2000169623A

  • METHOD FOR PURIFYING CRUDE BIS-beta-HYDROXYETHYL TEREPHTHALATE AND THE THUS PURIFIED BIS-beta-HYDROXYETHYL TEREPHTHALATE

    JP2002121173A

  • METHOD FOR PRODUCING BIS-beta-HYDROXYETHYL TEREPHTHALATE

    JP2003055300A

  • Method for producing polyester film

    JP2004175911A

  • Recycled polyester resin, depolymerization product of polyester, and method for producing the recycled polyester resin

    JP2005171138A